Fa’āliyyah Barnāmaj Taḥlīl al-Sulūkī al-Țaţbīqī Wifqan li al-Naẓriyyah al-Sulūkiyyah litaḥsīn Mustawā al-Dūbāmīn Ladai al-Aţfāl al-Maṣābīn biđţirābi Țaifi al-Tauḥīd: فعالية برنامج تحليل السلوكي التطبيقي وفقا للنظرية السلوكية لتحسين مستوى الدوبامين لدى الأطفال المصابين باظطراب طيف التوحيد - Mustafa, Iman Mohammed; Ali, Nizar Ismat (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study aimed to investigate the effectiveness of Applied Behavior Analysis (ABA) program according to behavioral theory in improving dopamine levels in children with autism spectrum disorder. The study sample consisted of (14) children with autism spectrum disorder in the experimental group. The experimental method with pre-post test design was used. Dopamine levels were measured through analysis of homovanillic acid (HVA) using ELISA technique. The results showed statistically significant differences at the level of (0.05) between pre and post measurements in favor of the post measurement, where the mean increased from (4.285) to (5.3349). The calculated t-value was (3.041) which is greater than the tabulated value (2.160). The effect size was (0.813) indicating high effectiveness of the program. The study recommends implementing ABA program as a therapeutic intervention to improve dopamine levels and integrating neurobiological and behavioral interventions in rehabilitation programs for children with autism spectrum disorder.